Educational Mismatch and Firm Productivity: Do Skills, Technology and Uncertainty Matter? - Benoît Mahy; François Rycx; Guillaume Vermeylen (Institute for the Study of Labor (IZA), 2015)
The authors provide first evidence on whether the direct relationship between educational mismatch and firm productivity varies across working environments. Using detailed Belgian linked employer-employee panel data for 1999-2010, they find the existence of a significant, positive (negative) impact of over- (under-)education on firm productivity. Moreover, their results show that the effect of over-education on productivity is stronger among firms: (i) with a higher share of high-skilled jobs, (ii) belonging to high-tech/knowledge-intensive industries, and (iii) evolving in a more uncertain economic environment. Interaction effects between under-education and working environments are less clear-cut. However, economic uncertainty is systematically found to accentuate the detrimental effect of under-education on productivity.
Keywords: J21; J24; 330; educational mismatch; productivity; linked employer-employee panel data; working environments